Yale Global Tic Severity Scale (YGTSS): Psychometric Quality of the Gold Standard for Tic Assessment Based on the Large-Scale EMTICS Study - Haas, Martina; Jakubovski, Ewgeni; Fremer, Carolin; Dietrich, Andrea; Hoekstra, Pieter J.; Jäger, Burkard; Müller-Vahl, Kirsten R.; , The EMTICS Collaborative Group; Apter, Alan; Baglioni, Valentina; Ball, Juliane; Benaroya-Milshtein, Noa; et al. (Frontiers in Psychiatry, 2021)
The Yale Global Tic Severity Scale (YGTSS) is a clinician-rated instrument considered as the gold standard for assessing tics in patients with Tourette’s Syndrome and other tic disorders. Previous psychometric investigations of the YGTSS exhibit different limitations such as small sample sizes and insufficient methods. To overcome these shortcomings, we used a subsample of the large-scale “European Multicentre Tics in Children Study” (EMTICS) including 706 children and adolescents with a chronic tic disorder and investigated convergent, discriminant and factorial validity, as well as internal consistency of the YGTSS. Our results confirm acceptable convergent and good to very good discriminant validity, respectively, indicated by a sufficient high correlation of the YGTSS total tic score with the Clinical Global Impression Scale for tics (rs = .65) and only low to medium correlations with clinical ratings of Attention Deficit/Hyperactivity Disorder symptoms and Obsessive-Compulsive Disorder symptoms (rs = .24 and rs = .27, respectively). Internal consistency was found to be lower than in previous studies, but still acceptable (Ω = .58). A confirmatory factor analysis supports the concept of the two factors “motor tics” and “phonic tics”, but still demonstrated just a marginal model fit (root mean square error of approximation = 0.09 [0.08; 1.00], comparative fit index = 0.90, and Tucker Lewis index = 0.87). A subsequent analysis of local misspecifications revealed correlated measurement errors, suggesting difficulties in differentiating between items as well as anchor points. In conclusion, our results indicate acceptable psychometric quality of the YGTSS. However, taking the wide use and importance of the YGTSS into account, further improvements are recommended such as a reduction of complexity of the YGTSS. In addition, our results show limitations of the global severity score as a sum score indicating that the separate use of the total tic score and the impairment rating is more beneficial.